2007
DOI: 10.1007/s10681-007-9394-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait locus for leaffolder (Cnaphalocrocis medinalis (Guenée)) resistance in rice on linkage group 1 based on damage score and flag leaf width

Abstract: Rice leaffolder (RLF) (Cnaphalocrocis medinalis (Guené e) is a destructive and widespread insect pest throughout the rice growing regions in Asia. The genetics of resistance to RLF in rice is very complex and not thoroughly explored. The present study was conducted to detect the quantitative trait loci (QTL) associated with RLF resistance involving 176 recombinant inbred lines (RILs) of F 8 generation derived from a cross between IR36, a leaffolder susceptible variety and TNAULFR831311, a moderately resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…However, Marathi et al (2012) reported that RM5709 marker was linked with qSPP-4.1 , indicating the pleiotropic effect of qPL4.1 on panicle length. The present study reported that a total of 14 SSRs were associated with FLW out of them 3 SSRs RM297, RM5709, RM1132) were reported previously [28,29,31,67,68]. Four SSRs, RM447, RM297, RM5709 and RM285 have been identified for flag leaf length (FLL) in QTL regions of qFLL8.1 , qFLL-1.1 [29], qFLL-4.1a and qFLL9.1 , respectively.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, Marathi et al (2012) reported that RM5709 marker was linked with qSPP-4.1 , indicating the pleiotropic effect of qPL4.1 on panicle length. The present study reported that a total of 14 SSRs were associated with FLW out of them 3 SSRs RM297, RM5709, RM1132) were reported previously [28,29,31,67,68]. Four SSRs, RM447, RM297, RM5709 and RM285 have been identified for flag leaf length (FLL) in QTL regions of qFLL8.1 , qFLL-1.1 [29], qFLL-4.1a and qFLL9.1 , respectively.…”
Section: Discussionmentioning
confidence: 61%
“…The present study reported that a total of 14 SSRs were associated with FLW out of them 3 SSRs RM297, RM5709, RM1132) were reported previously [28,29,31,67,68]. Four SSRs, RM447, RM297, RM5709 and RM285 have been identified for flag leaf length (FLL) in QTL regions of qFLL8.1 , qFLL-1.1 [29], qFLL-4.1a and qFLL9.1 , respectively. Out of the above, two markers, RM297 and RM5709 were also associated with QTLs for flag leaf width(FLW), qFLW-1.1 and qFLW4.1 , respectivelly due to pleiotropic effects [28, 29].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Recently, internal transcribed spacer (ITS) markers were developed to identify and distinguish the different Antrodia species (Chiu 2007). However, microsatellites or simple sequence repeats (SSRs) were commonly used for diversity analysis, quantitative trait loci (QTL) mapping and population genetic studies of many organisms (Thomson et al 2007;Selvaraju et al 2007;Zhang et al 2008) because of their abundance, multiallelic nature, co-dominance, easily detectable nature and reproducibility. As the development of genomic SSR markers are expensive, resource intensive and time consuming, highly transferable expressed sequence tag (EST)-derived SSR markers can be used to evaluate the genetic variation of transcribed genes in A. cinnamomea.…”
mentioning
confidence: 99%